China’s Island Frontier: Geographical Ideas on the Continent-based Nationalist Narratives on Taiwan - Peter Kang (Island Studies Journal, 2011)
This paper explores how nationalist narratives from Taiwan grappled with incorporating their ‘island frontier’ into conceptions of a Chinese unitary state. In the post World War II era, after the Chinese Nationalist government-in-exile re-established itself on the island of Taiwan, US-dominated scholarship strategically framed Taiwan as a convenient substitute for the study of China. This framing went hand in hand with the re-sinicization project on the island vigorously pursued by the Nationalists after they took control over the island after the collapse of the Japanese Empire. The Nationalist agenda emphasized the historical connection between the island and mainland China in order to politically create an imagined, and imagining, national community across the Strait. This paper critically investigates how continent-based nationalist narratives have sought to incorporate offshore islands into their unitary framework. It does so by deploying the concepts of geobody, geomancy, geochronology, geosymmetrical analogies, and regional demarcation to explore the geographical ideas on the construction of the postwar national imaginary.